Pengungkapan Corporate Social Responsibility Berdasarkan Global Reporting Initiative 3.1 di Indonesia - Handrian, Irfan; Fahmi, Idqan (Universitas Brawijaya, Indonesia, 2015)
This research objectives are (1) Assess the level of CSR in public companies in Indonesia based on their sustainability reports (2) Suggest improvements for CSR assessment framework. Based on secondary data obtained from Companies sustainability reports registered on the Stock Exchange. Through descriptive analysis method and the AHP weighting scale to see the priority of parameter. CSR in Indonesia during the year 2007-2012 showed a small percentage of CSR reporting, proving the laws are still weak, low motivation on the part of the company and the low influence of stakeholders (stakeholders). According to the results of the company-s CSR reporting based on GRI 3.1 in Indonesia, has a value of B and A +. Mapping CSR pyramid based company Caroll in Indonesia shows that the company including the philanthropic category is an important sector is the mining sector; infrastructure, utilities and transportation; and consumer goods industries.